APPLICATION OF OZONE-SLURRY ICE COMBINED SYSTEM FOR MAINTAINING THE FRESHNESS OF RED TILAPIA AND SHORT-BODIED MACKEREL DURING COLD STORAGE - Tri Winarni Agustini; Muhammad Nur; Endang Kusdiyantini (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Application of ozone combined with the chilling system on preserving fresh fish has obviously brought about more advantages. This study observed the application of an ozone-slurry ice combined system for maintaining the freshness of two different fishes during storage. The fishes used were red tilapia (Oreochromis niloticus) and short-bodied mackerel (Scomberomorus rastrelliger), using ozone and slurry ice. The experimental design used was factorial using a completely randomized design employed with an ozone concentration of 0 ppm and 3.5 ppm with storage times of 0, 4, 8, 12, and 16 days. The parameters observed included: peroxide value (PV), total volatile base nitrogen (TVBN), total viable count (TVC), and a sensory test. The parametric data were analyzed using ANOVA and followed by least significant difference (LSD), whereas the non-parametric data were analyzed using the Kruskal Wallis test followed by multiple comparison tests. Ozone and slurry ice treatment of different concentrations had a significant (p<0.05) effect on the TVBN, the PV, and the TVC. The interaction of ozone and slurry ice provided no significant  difference (p>0.05) in both samples.A sensory evaluation in both samples showed good correlation with TVC. This study showed that ozone and slurry ice could  maintain the samples freshness during storage.